2008
DOI: 10.1007/978-0-387-78952-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of Innate Immunity by Periodontopathic Bacteria via Exploitation of Complement Receptor-3

Abstract: The capacity of certain pathogens to exploit innate immune receptors enables them to undermine immune clearance and persist in their host, often causing disease. Here we review subversive interactions of Porphyromonas gingivalis, a major periodontal pathogen, with the complement receptor-3 (CR3; CD11b/CD18) in monocytes/macrophages. Through its cell surface fimbriae, P. gingivalis stimulates Toll-like receptor-2 (TLR2) inside-out signaling which induces the highaffinity conformation of CR3. Although this activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 64 publications
2
36
0
1
Order By: Relevance
“…Similarly, singlespecies infection using 10 7 CFU of P. gingivalis caused a small but not statistically significant increase in bone loss over shaminfected animals. Overall, these results are consistent with previous results from Baker et al (3) and our prior studies (17,37) that showed that infection using 10 9 CFU of P. gingivalis was required to induce significant levels of bone resorption. Interestingly, dual-species infection with 10 9 CFU of S. gordonii followed by 10 7 CFU of P. gingivalis induced significant bone loss, similar to that observed in the prior single infection experiments using 10 9 CFU of P. gingivalis (17,37).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, singlespecies infection using 10 7 CFU of P. gingivalis caused a small but not statistically significant increase in bone loss over shaminfected animals. Overall, these results are consistent with previous results from Baker et al (3) and our prior studies (17,37) that showed that infection using 10 9 CFU of P. gingivalis was required to induce significant levels of bone resorption. Interestingly, dual-species infection with 10 9 CFU of S. gordonii followed by 10 7 CFU of P. gingivalis induced significant bone loss, similar to that observed in the prior single infection experiments using 10 9 CFU of P. gingivalis (17,37).…”
Section: Discussionsupporting
confidence: 92%
“…There is no IgG or complement involved in PepO-induced phagocytosis by macrophages. Increasing evidence shows that CR3 is also a multifunctional pattern recognition receptor of the innate immune system (40)(41)(42)(43). Once activated by its ligand, CR3 mediates a series of signaling transductions, including rearrangement of actin, which promotes phagocytosis of bacteria by macrophages and contributes to the host defense response to bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tight control of neutrophil functions and survival after bacterial clearance by induction of apoptosis, immune tolerance and resolution of inflammation, exert protective effects toward the host tissues against inflammatory tissue damage. A failure to properly regulate neutrophil abundance and turnover directly contributes to the pathogenesis of periodontitis and current literature implicates neutrophils as the main immune cell type responsible for periodontal disease progression (Hajishengallis et al, 2008b, 2015a; Scott and Krauss, 2012). …”
Section: Neutrophils In Periodontitismentioning
confidence: 99%